The Role of Brand Love in Mediating the Influence of Brand Image on Brand Advocacy - Fahmi Afif Fakhrudin Rahmad; Fikriah, Nur Laili (Mabsya: Jurnal Manajemen Bisnis Syariah, 2026)
Increasingly fierce retail competition demands businesses to build long-term relationships with consumers. Brand advocacy is a strategic behavior because it generates credible promotions based on consumer experiences. However, previous research findings on the influence of brand image on brand advocacy have shown inconsistent results. Therefore, this study aims to analyze the influence of brand image on brand advocacy, with brand affection as a mediating variable, in a agricultural retail store context. This study uses a quantitative approach with a survey method involving 130 UD Rahmad consumers selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the measurement and structural models. The results indicate that brand image has a positive and significant influence on brand advocacy and brand affection. Brand affection also has a positive and significant influence on brand advocacy and is proven to partially mediate the relationship between brand image and brand advocacy. These findings confirm that brand affection acts as an affective mechanism that strengthens the influence of brand image on advocacy behavior. This study concludes that strengthening brand image and managing consumer emotional attachment are important strategies for agricultural retail store ers in driving sustainable brand advocacy.